Profil Guru Penjas SD Kecamatan Dukuhturi Kabupaten Tegal Tahun 2021 - Satrio, Muhamad Suria; Irsyada, Roas (Universitas Negeri Semarang, 2023)
The purpose of this study is to describe the profile of elementary school physical education teachers in Dukuhturi District, Tegal Regency and to find out and analyze the views of elementary school physical education teachers in Dukuhturi District, Tegal Regency in 2021 regarding 4 standard teacher competencies. The method used in this research is descriptive qualitative. The research location is in the Dukuhturi District, Tegal Regency. The results of this study are a clear picture of the condition of the profile and competence of physical education teachers in the Dukuhturi District, Tegal Regency in 2021 which was obtained through interviews, observations and also documentation. From the results of interviews and observations that I have made of physical education teachers in the Dukuhturi District, Tegal Regency, they are quite good at understanding the 4 teacher competency standards (pedagogic, personality, social, and professional competencies). The conclusion of this study is that teachers are able to know what to do during the pandemic in teaching and learning activities so that students remain enthusiastic and enthusiastic in participating in learning. The competencies possessed are also good in terms of pedagogics and professionals, as well as very good in terms of social and personality.